The impact of foreign direct investment on income inequality in developing countries: The Bayesian approach - Gam, To Thi Hong; Oanh, Dao Le Kieu; Dang, Nguyen Mau Ba (Jurnal Ekonomi & Studi Pembangunan, 2023)
Inequality in general and income inequality in particular have existed for a long time and tend to increase daily. Foreign direct investment (FDI) is expected to be an important factor contributing to mitigating that situation. However, the results of previous empirical studies on the impact of FDI on income inequality have not reached a consistent conclusion. Therefore, this study evaluated the impact of foreign direct investment on income inequality in developing economies. The study has provided evidence that the relationship is nonlinear through data from a sample of 36 developing countries between 2008 and 2020 and the Monte-Carlo algorithm according to the Bayesian approach. We document a U-shaped effect of FDI on income inequality. Besides, other factors, including trade openness and migration, obviously impact income inequality. Different results were found when FDI interacted with trade or migration, representing important channels through which inequality is affected. With these results, we suggest that policymakers in developing countries should develop appropriate policies on FDI attraction encourage trade openness and migration to reduce income inequality.